Once-nightly sodium oxybate (FT218) improved symptoms of disrupted nighttime sleep in people with narcolepsy: a plain language summary - Thomas Roth; Michael J Thorpy; Clete A Kushida; Matthew Horsnell; Jennifer Gudeman (Becaris Publishing Limited, 2023)
What is this summary about? This is a plain language summary of a published article in the journal CNS Drugs. Narcolepsy is a rare sleep condition. Most people with narcolepsy experience disrupted nighttime sleep and have poor quality of sleep. Sometimes these symptoms are not easily diagnosed as a symptom of narcolepsy. Sodium oxybate is an approved treatment for narcolepsy. The only version of sodium oxybate that was available until 2023 required people to take their sodium oxybate at bedtime and then again in the middle of the night. The US Food and Drug Administration (FDA for short) has approved a once-nightly bedtime dose of sodium oxybate (ON-SXB for short, also known as FT218 or LUMRYZ™) to treat symptoms of narcolepsy in adults. These symptoms are daytime sleepiness and cataplexy, which is an episode of sudden muscle weakness. The once-nightly bedtime dose of ON-SXB removes the need for a middle-of-the-night dose of sodium oxybate. The REST-ON clinical study compared ON-SXB to a placebo (a substance that contains no medicine) to determine if it was better at treating symptoms of disrupted nighttime sleep associated with narcolepsy. This summary looks at whether ON-SXB was better than placebo at treating symptoms of disrupted nighttime sleep. What were the results? Compared to people who took placebo, people who took ON-SXB had fewer number of changes from deeper to lighter sleep stages and woke up less during the night. They also reported that they slept better at night and felt more refreshed when waking up in the morning. People with narcolepsy sometimes take alerting agents to help with sleepiness during the day, but alerting agents can cause difficulty sleeping at night. This study showed that people who took ON-SXB had better nighttime sleep even if they were taking alerting agents during the day. The most common side effects of ON-SXB included dizziness, nausea (feeling sick to your stomach), vomiting, headache, and bedwetting. What do the results mean? A once-nightly bedtime dose of ON-SXB is a narcolepsy treatment option for people without the need for a middle-of-thenight dose of sodium oxybate.